Antibacterial Activity of The Nucleoside Antibiotic (NA) Isolated from Streptomyces alboflavus - T.K. Aldaly, Zainab (University of Thi-Qar Journal of Science, 2019)
During this study a new antibiotic was isolated from Streptomyces alboflavus which was active against Gram-positive and Gram-negative bacteria .The isolate antibiotic was white crystalline powder at (28-30)C˚. Physicochemical properties were studied includes TLC, IR spectroscopy and Uv spectrum as well as color tests, all these studies indicate that the antibiotic produced by Streptomyces sp. Is a nucleoside antibiotic and gave the name (NA).The minimal inhibitory concentration of produced nucleoside antibiotic were determined against five standard gram positive positive and gram negative bacteria with MIC value ranged (2-25) µ/ml .